2007
DOI: 10.1002/ana.21192
|View full text |Cite
|
Sign up to set email alerts
|

Tau and α‐synuclein in susceptibility to, and dementia in, Parkinson's disease

Abstract: Our data support the hypothesis that tau and alpha-synuclein are involved in shared or converging pathways in the pathogenesis of PD, and suggest that the tau inversion influences the development of cognitive impairment and dementia in patients with idiopathic PD. These findings have potentially important implications for understanding the interface between tau and alpha-synuclein pathways in neurodegenerative disorders and for unraveling the biological basis for cognitive impairment and dementia in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
221
4
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(237 citation statements)
references
References 43 publications
6
221
4
3
Order By: Relevance
“…[23][24][25] Previous studies have shown that genetic risk factors, including variations in microtubule-associated protein tau (MAPT), 26 ␣-synuclein (SNCA), 26 and catechol-O-methyltransferase (COMT) 27,28 may explain some of the heterogeneity in cognitive performance in PD. We and others have shown that GBA mutations are associated with cortical Lewy body pathology.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] Previous studies have shown that genetic risk factors, including variations in microtubule-associated protein tau (MAPT), 26 ␣-synuclein (SNCA), 26 and catechol-O-methyltransferase (COMT) 27,28 may explain some of the heterogeneity in cognitive performance in PD. We and others have shown that GBA mutations are associated with cortical Lewy body pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Tau and α-synuclein likely play pivotal roles in disparate sets of neurodegenerative diseases (25). Mutations in their genes, MAPT and SNCA, that lead to formation of tau and α-synuclein, respectively, result in Alzheimer's disease, PD, DLB, and frontotemporal dementia (21,25,34). Although the mechanisms by which these proteins aggregate appear to be different, α-synuclein, for example, is spontaneously self-polymerizing (35), whereas tau requires the presence of an inducing agent (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…63 Genetic variability in the a-synuclein gene is a risk factor for the development of Parkinson's disease. [64][65][66][67][68] Null mutant mice lacking a-synuclein exhibit a lower locomotor response to amphetamine, 69 whereas transgenic animals overexpressing a-synuclein display signs of motor impairment associated with a decrease in tyrosine hydroxylase levels. 70 These data suggest that a-synuclein downregulates dopaminergic neurotransmission, possibly by inhibiting tyrosine hydroxylase activity.…”
Section: Discussionmentioning
confidence: 99%